Accidental ingestion of a barbed wire broach and its endoscopic retrieval: Prevention better than cure - Rajashekar Mohan; Sreesha Rao; Mathew Benjamin; Radhakrishna K Bhagavan (Wolters Kluwer Medknow Publications, 2011)
Ingestion of instruments is a potential complication that can occur during dental procedures. We report a case of accidental ingestion of an endodontic barbed wire broach during root canal treatment and its subsequent retrieval by endoscopic methods. Although prevention is the best approach, proper management of such an event is also crucial. The objective of this report is to draw attention to the potentially serious complications that can occur if preventive techniques are not practised, and to discuss the accepted guidelines for management of such an event.